2020
DOI: 10.1002/hec.3990
|View full text |Cite
|
Sign up to set email alerts
|

The effect of physical education on children's body weight and human capital: New evidence from the ECLS‐K:2011

Abstract: This study provides evidence on the impact of physical education on child body weight, cognitive, and noncognitive achievement using data from the Early Child Longitudinal Survey Kindergarten Class of 2010‐2011 (ECLS‐K: 2011). Students in the 2011 cohort were exposed to increased accountability pressures by No Child Left Behind, yet average weekly physical education time has not decreased from that reported in studies using the original ECLS‐K class of 1998‐1999. We instrument for teacher‐reported weekly PE ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
(112 reference statements)
0
9
0
Order By: Relevance
“…Together with its role in maintaining body energy balance, it can also control and treat chronic noncommunicable diseases like overweight and obesity. It achieves this by maintaining the body mass index (BMI) [ 3 ]. Physical activity also proves to be an essential aspect of musculoskeletal, metabolism, cardiovascular system, and, generally, the body's development processes.…”
Section: Introductionmentioning
confidence: 99%
“…Together with its role in maintaining body energy balance, it can also control and treat chronic noncommunicable diseases like overweight and obesity. It achieves this by maintaining the body mass index (BMI) [ 3 ]. Physical activity also proves to be an essential aspect of musculoskeletal, metabolism, cardiovascular system, and, generally, the body's development processes.…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis does have limitations. Although BMI was carefully measured, time in PE and recess was measured coarsely and inconsistently across different cohorts, making it challenging in some cases to tell whether a school had complied with state laws 11 or whether PE and recess increased or decreased between the older and younger cohorts. We addressed the coarse measurement of time by using interval regression, but our interval regression model assumed that residuals are normal and homoscedastic, and departures from those assumptions might have introduced bias 23…”
Section: Resultsmentioning
confidence: 99%
“…Although past studies also found that schools often fail to comply with state laws for PE time, 10,11,28 the finding that changes to state law failed to cause any increase in the time spent in PE or recess is a bit startling. There are several possible explanations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These families lack the financial and care support for healthy child development. Education is critical to reducing poor health 3. Children’s academic achievement was associated with further educational attainment and working performance in the labour market 4.…”
Section: Introductionmentioning
confidence: 99%